Calculation of liver-to-blood inocula, parasite growth rates, and preerythrocytic vaccine efficacy, from serial quantitative polymerase chain reaction studies of volunteers challenged with malaria sporozoites. - Bejon, P; Andrews, L; Andersen, R; Dunachie, S; Webster, D; Walther, M; Gilbert, S; Peto, T; Hill, A (2005)
We calculated the number and growth rate of Plasmodium falciparum parasites emerging in recipients of candidate preerythrocytic malaria vaccines and unvaccinated control subjects undergoing mosquito-bite challenge. This was done to measure vaccine efficacy and to distinguish the effects on blood-stage multiplication from those on liver-stage parasites. Real-time polymerase chain reaction measurements of parasite densities were analyzed by nonlinear regression and mixed-effects models. Substantial reductions in numbers of liver parasites resulted from the use of 2 immunization regimens: FP9 boosted by modified virus Ankara (MVA) encoding the malaria epitope-thrombospondin-related adhesion protein insert (92% reduction) and RTS,S/AS02 used in heterologous prime-boost immunization regimens, with MVA encoding the circumsporozoite protein (97% reduction). Forty-eight-hour growth rates in blood from control subjects were not different from those in blood from any vaccination group (mean, 14.4-fold [95% confidence interval, 11-19-fold]).